Electrical modeling and simulation of industrial power system with Matlab/Simulink program - Aree, Pichai; Nakawiro, Worawat (My University, 2013)
Power system dynamic simulations have been traditionally constrained to commercial package tools. While these tools are mostly efficient for large scale simulation, their component models are often encapsulated, and not possible to be examined and modified. For educational use, it is more important that the component modeling is transparent and flexible. Hence, in this paper, an object-oriented simulation of an industrial power system is constructed in Matlab/Simulink environment. The step-by-step implementation of Simulink block diagram model describing power system devices is fully given in detail. This presented approach is well suited to educational purpose in a way that students are able to modify their models and get quick start their simulations. The dynamic simulations with result and discussion are given through illustrative case study of voltage sag.
Keywords: Induction motor; Industrial power system; Matlab/Simulink; Object-oriented simulation